Comparison of Healthcare Encounters and Drug Persistence in Patients With Pulmonary Arterial Hypertension Receiving Oral Selexipag, Inhaled Iloprost, or Parenteral Treprostinil: A Retrospective Database Analysis - Ci Song; Peter Kunovszki; Amélie Beaudet (Journal of Health Economics and Outcomes Research)
**Background:** Agents targeting the prostacyclin (PGI~2~) pathway are important in managing pulmonary arterial hypertension (PAH). No head-to-head clinical trials have compared outcomes between the 3 different PGI~2~-pathway drugs most commonly available in countries with advanced healthcare: oral selexipag, inhaled iloprost, and parenteral (subcutaneous or intravenous) treprostinil.